The urgency of basketball athletes' self-confidence in facing the game: A literature review study - Aditya Harja Nenggar; Arsika Yunarta (International Journal of Basketball Studies, 2023)
In human life, health is crucial because it is one of the important aspects in carrying out various activities. If the body is not healthy, it will experience problems such as decreased physical condition and obstacles to activity. In Indonesia alone, basketball is the fastest growing sport, so many clubs show their existence, even at the elementary, middle, high school, and college levels there are their own basketball clubs, either for leisure, hobbies, or pursuing achievements. Not only physical health conditions are considered, but mental health conditions are no less important. The purpose of this research is to find out what the urgency of basketball athletes' confidence in facing the match is like. The type of research used is descriptive qualitative with a literature study method. The writing of this article is carried out to examine the urgency or importance of self-confidence possessed by athletes, especially basketball athletes in facing matches. There will be a lot felt by basketball players when the match takes place, even before competing, they must experience anxiety. An athlete must have good self-confidence to reduce this anxiety, so that anxiety can be defeated. The results of the study revealed that self-confidence can be honed through positive thinking, simulation exercises, and self-talk.